Faktor-Faktor dan Peran Efikasi Diri dalam Praktik Ketidakjujuran Akademis pada Mahasiswa - Negara, Mayuning Candra; Negara, Hastining Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2025)
The widespread discussion regarding assignment and thesis jockey services among students has raised concerns about the low level of honesty of the nation's next generation. Assignment and thesis jockeying services refer to academic dishonesty behavior. Academic dishonesty is an act of deception or cheating, which aims to obtain learning assessments that are in accordance with individual wishes through various means. This research aims to determine the factors that play a role in acts of academic dishonesty among students, as well as to determine the role of self-efficacy in prevents acts of academic dishonesty. This research uses a literature study method, by reviewing 10 empirical research articles that meet the inclusion criteria. The factors that play a role in acts of academic dishonesty include: self-efficacy, academic anxiety, self-monitoring, morality, learning motivation, self-regulated learning, procrastination, and religiosity.